The Impact of Carbon Emission Disclosure on Firm Valuation: Exploring the Moderating Role of Foreign Ownership - Ni Putu Mia Triskasari Putri; Naniek Noviari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The value of a firm, as reflected in fluctuations of the composite stock price index, is influenced by various factors, including carbon emission disclosure, which has garnered increasing attention from stakeholders due to concerns over global warming. This research investigates the impact of carbon emission disclosure on firm value, with foreign ownership as a moderating variable. The study focuses on energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. A purposive sampling method was used to select the research sample, resulting in 84 observations. The theoretical framework of this study is grounded in signaling theory, legitimacy theory, and agency theory. Data analysis was conducted using Moderated Regression Analysis (MRA) through EViews software. The findings reveal that carbon emission disclosure has a negative effect on firm value. Furthermore, the results indicate that foreign ownership does not strengthen the relationship between carbon emission disclosure and firm value.